Ideas and Practices for the Social Management of Territories of Citinzenship.: The Case of the Borborema Territory, Paraiba - Caniello, Márcio; Piraux, Marc; Bastos, Valério Veríssimo de Souza (Sustainability in Debate, 2013)
The Territories of Citizenship Program aims to strengthen small-scale farmers in Brazil by financing productive projects and infrastructures defined within deliberative institutional arrangements which is implementing the so-called “cycle of social management”. It presupposes dialectic active and progressive between the social capital of the territory, collective participation and project implementation, resulting in a virtuous process and sustainable rural development. The Territory of Borborema, in the state of Paraiba, was created in 2003 with a high level of social capital and one process of consolidation ofpeasant social movements and agroecological transition. However, it does not show a good performance in terms of implementation of investment projects. This paper analyse this apparent paradox making relationship between the ideology of the government and the practice of social actors within the territorial device.